Representações acerca de mulheres em textos que compõem o material didático de língua portuguesa no ensino médio - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This study investigates the representations of women in high school teaching materials. It focuses on the way women are portrayed in the texts selected to compose these works. To this end, the general objective of this research is to critically analyze the presence and configuration of female characters in the textbooks Se Liga Nas Linguagens – Volume Único and in the material Revisa Goiás. The methodology used is qualitative, based on documentary analysis and bibliographic review. Content analysis, based on Fairclough (2001), allows us to identify discursive patterns that guide the construction of gender identities in teaching materials. In addition to the textual examination, the study discusses the pedagogical consequences of these representations, since it is understood that the school is a space for the reproduction of discourses, but it can also function as a place of resistance (Louro, 2004). The adopted approach considers the need to consciously select works that promote diversity and question stereotypes rooted in school culture. As contributions, it allowed a debate on gender equity in education, highlighting the need for more careful choices in the selection of texts that make up teaching materials. Furthermore, it promoted reflections on more inclusive pedagogical practices, favoring a learning environment that values diversity and gender equity
Representations of women in literary texts featured in portuguese language teaching materials for high school
Keywords: Ensino médio - Livro didático - Estereótipos de gênero; Livro didático - Ensino médio - Representações de mulheres; High school - Gender stereotypes - Textbook; Textbook - Representations of women; CIENCIAS HUMANAS::EDUCACAO